Implementation of the SAW and TOPSIS Methods as a Decision Support System in the Election of Outstanding TNI Members - Niqotaini, Zatin; Vernanda, Dwi (Universitas Insan Cendekia Mandiri, 2024)
This research aims to apply the SAW and TOPSIS methods in the decision support system for the selection of outstanding members at the TNI Maritime Data Information Center. The selection of outstanding members is an important activity that aims to reward individual performance and improve the quality of human resources. In this study, the authors realize that the conventional method used in the selection of outstanding members requires significant time and cost. Therefore, the researcher seeks to apply the SAW and TOPSIS methods to achieve transparent, effective, and objective elections. Today's technological advances play an important role in various aspects of human life, including education, economics, business, and other organizations. Previous research has shown that the SAW and TOPSIS methods have given good results in the selection and ranking process. In this study, the author will use the SAW and TOPSIS methods to select outstanding members in the TNI Pusinformar. The results of previous studies showed that the SAW method had an accuracy of 45%, while the TOPSIS method had an accuracy of 60%. Therefore, this research is expected to contribute to improving the quality of TNI members and facilitating the process of selecting outstanding members. Decision support systems that use the SAW and TOPSIS methods can be an effective tool in selecting outstanding members based on predetermined criteria. It is hoped that the results of this study can provide more accurate and objective recommendations in the selection of outstanding members in the TNI Pusinformar.